2017
DOI: 10.1371/journal.pone.0189818
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Map3k7 activates sinoatrial node-like differentiation in mouse ES-derived cardiomyocytes

Abstract: In vivo, cardiomyocytes comprise a heterogeneous population of contractile cells defined by unique electrophysiologies, molecular markers and morphologies. The mechanisms directing myocardial cells to specific sub-lineages remain poorly understood. Here we report that overexpression of TGFβ-Activated Kinase (TAK1/Map3k7) in mouse embryonic stem (ES) cells faithfully directs myocardial differentiation of embryoid body (EB)-derived cardiac cells toward the sinoatrial node (SAN) lineage. Most cardiac cells in Map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Similarly, beat rate can be determined by hand counting the number of beats per unit of time and converting this into beats per minute (bpm). This method is time consuming and prone to human error, particularly for fast beating cardiac cells, such as SAN cells [15]. In addition, cardiac cells may pause during imaging, which could be triggered by changes in temperature, changes in light intensity, interference from other beating areas in the dish, or experimental manipulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, beat rate can be determined by hand counting the number of beats per unit of time and converting this into beats per minute (bpm). This method is time consuming and prone to human error, particularly for fast beating cardiac cells, such as SAN cells [15]. In addition, cardiac cells may pause during imaging, which could be triggered by changes in temperature, changes in light intensity, interference from other beating areas in the dish, or experimental manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…Given the recent success with the implantation of ventricular cardiomyocytes, it now seems feasible to generate SAN cells in vitro for use as biological pacemakers; however, again, this will require protocols for the efficient differentiation of pure pacemakers from pluripotent sources. Early work in this field suggests that this can be accomplished by the addition of small molecules and growth factors as cells differentiate in vitro [12][13][14][15], however much work remains to be done. One tool that is currently lacking is the ability to rapidly distinguish cardiac subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Map3k7-overexpressing cell lines were transduced with the overexpression vector, hPGK::Map3k7-IRES-GFP. Clonal lines were established and checked for constitutive overexpression of Map3k7 by qRT-PCR both in undifferentiated ES cells and in differentiating EBs [17]. All lines were maintained in ES cell growth medium (10% ES-qualified FBS, 2 mM glutamine, 0.1 mM non-essential amino acids, 1 mM sodium pyruvate, 10 −4 mM β-mercaptoethanol, 1× pen/strep, and 1000 units LIF).…”
Section: Cell Culturementioning
confidence: 99%
“…Mice with cardiac-specific expression of a dominant interfering form of Map3k7 die shortly after birth due to conduction system abnormalities [16]. In addition, we recently showed that myocardial differentiation within Map3k7-overexpressing EBs is directed toward the sinoatrial node (SAN) lineage [17]. Taken together, these data suggest a role for Map3k7 in both the establishment and patterning of heart tissue, but its mechanism of action is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation